Designing Communicative-Based Arabic Learning Materials to Enhance 21st Century Skills of Students in Thailand - Qorin, Amami Shofiya Al; Mahliatussikah, Hanik; Sumalee, Yussara (Journal of Arabic Language Studies and Teaching, 2025)
This study aims to develop Arabic learning materials based on communicative approaches to enhance the 21st-century skills of students in Thailand. The research used the ADDIE model, which includes five steps: analyzing student needs, designing materials, developing content and media, implementing the materials in the classroom, and evaluating their effectiveness. Data were collected from students, teachers, and experts using questionnaires, interviews, and classroom observations. The results show that the materials significantly improved students' speaking confidence (78.4%) and listening comprehension (81.2%). Expert validation, teachers' and students' responses yielded a feasibility score of 84,3%, confirming the materials' content, language, and presentation quality. Additionally, the materials encouraged collaboration, critical thinking, and communication, essential components of modern education. This study offers practical contributions to Arabic language teaching by providing learning resources that are not only communicative but also aligned with 21st-century educational demands and student-centered learning principles.